The Roles of Psychological Inflexibility and Mindful Awareness on Distress in a Convenience Sample of Black American Adults in the United States - Akihiko Masuda; Bradley L. Goodnight; Nicole E. Caporino; Cerila C. Rapadas; Erin C. Tully (Behavioral Sciences)
Background: In recent years, the conceptual framework of psychological flexibility/inflexibility has been of global interest in the field of behavioral health. Nevertheless, studies and evidence of psychological flexibility/inflexibility remain limited for underrepresented groups of individuals, including people of color in the United States (U.S.). Among these groups of individuals are Black Americans in the U.S. In response to this empirical gap, the present cross-sectional study investigated whether psychological inflexibility and mindful awareness were uniquely related to general psychological distress, somatization, depression, and anxiety in Black American adults in the United States. Methods: A convenience sample of 359 Black American college students completed self-report measures of interest online. Results: As predicted, correlational analyses showed that psychological inflexibility was positively associated with general psychological distress, somatization, depression, and anxiety, and that mindful awareness was negatively associated with these four distress variables. A path analysis model revealed that psychological inflexibility, but not mindful awareness, was uniquely associated with these distress variables. Conclusions: The present study extended previous findings with a convenience sample of Black American college students, suggesting that psychological inflexibility may be a useful construct for understanding psychological distress, more so than mindful awareness, among Black American adults in the U.S.